Electronic effects promoted the catalytic activities of binuclear Co(ii) complexes for visible-light-driven CO2 reduction in a water-containing system. Issue 14 (16th March 2023) - Su, Chao; Chen, Zilu; Feng, Qin; Wei, Fangsha; Mo, Anna; Huang, Hai-Hua; Hu, Huancheng; Zou, Huahong; Liang, Fupei; Liu, Dongcheng
Abstract : A new binuclear cobalt complex with electron-donating group (–OCH3 ) accelerates the visible-light-driven conversion of CO2 to CO in a water-containing system. Abstract : Under the action of a catalyst, the photoinduced reduction of CO2 to chemicals and fuels is one of the greenest and environment-friendly approaches for decreasing atmospheric CO2 emissions. Since the environment was affected by the greenhouse effect, scientists have never stopped exploring efficient photoinduced CO2 reduction systems, particularly the highly desired non-noble metal complexes. Most of the currently reported complexes based on non-noble metals exhibit low catalytic activity, selectivity, and stability in aqueous systems under the irradiation of visible light. Herein, we report a new binuclear cobalt complex [Co2 (L 1 )(OAc)2 ](OAc) (Co2 L 1, HL 1 = 2, 6-bis((bis(pyridin-2-ylmethyl)amino)methyl)-4-methoxyphenol), which accelerates the visible-light-driven conversion of CO2 to CO in acetonitrile/water (4/1, v / v ) nearly 40% more than that for the previously reported [Co2 (L 2 )(OAc)2 ](OAc) (Co2 L 2, HL 2 = 2, 6-bis((bis(pyridin-2-ylmethyl)amino)methyl)-4-( tert -butyl)phenol) by our research group. It has an excellent CO selectivity of 98%, and the TONCO is as high as 5920. Experimental results and DFT calculations showed that the enhanced catalytic performance of Co2 L 1 is due to the electron-donating effect of a methoxy group (–OCH3 ) in Co2 L 1 compared to a tertiary butyl group (–C(CH3 )3 ) in Co2 L 2, which reduces the energy barrier of the rate-limiting CO2 coordination step in the visible-light-driven CO2 reduction process.